Numerical investigation of free rotor aerodynamics - Sari, Sarih; Dogrul, Ali; Bayraktar, Seyfettin (YILDIZ TECHNICAL UNIV, 2024)
Rotor aerodynamics is important for rotary-wing aircraft especially those located in naval surface combatants. The aerodynamic interaction between the helicopter, its rotor and the ship structure should be investigated precisely. This study focuses on the aerodynamic performance of four-blade rotor geometry of Sikorsky S-76 helicopter. The main rotor geometry was analyzed numerically in the free condition in an unbounded flow domain. Unsteady Reynolds-Averaged Navier-Stokes (URANS) equations in rigid body motion (RBM) on unstructured grids were solved by discretizing the computational domain with finite volume elements and using the Shear-Stress Transport (SST) k-omega turbulence model. The numerical approach was verified using the GCI method and validated with the relevant data available in the literature. It was found that in hover condition, non-dimensional thrust and the torque coefficients change slightly with the rotation speed of the rotor due to possibly the collective pitch angle. However, whereas the torque coefficient varies slightly with rotor speed, the thrust coefficient fluctuates substantially.
Keywords: Aerodynamics; Free Rotor; GCI; Hover; URANS; Engineering